'Role' as an interactional device - Halkowski, Timothy (Social Problems, 1990)
This paper reports on an aspect of the social organization of interaction, namely, the use by interactants of the concept 'role.' In contrast with traditional social scientific uses of this concept as an explanatory resource in the analysis of social action, I propose that interactants use this concept to make sense of - as well as accomplish - actions and activities in the social world. Analysis of segments of conversation taken from the Iran-Contra Congressional hearings demonstrate this, as well as the more general point that description is a form of social action.
Keywords: Role, interaction, social theory, communication, conversation analysis, membership categorization, mcd analysis